(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
This article analyzes how the economy has changed during the digital transformation period, international indices for measuring digitalization (DESI, NRI, EGDI, GCI, etc.) and examines the process of transition to a new economic model on the example of Azerbaijan. The introduction justifies the relevance of the topic, explains the features of digitalization. Information is provided on various aspects of digitalization and the indices that measure them, and international studies are highlighted in the literature review. The article presents digital development indicators for Azerbaijan. Finally, the results obtained are summarized and proposals for the development of digitalization are put forward. Keywords: new economy, digitalization, index, international rating, measurement